The Role of Interpersonal Influence in Counterbalancing Psychopathic Personality Trait Facets at Work. (April 2018) - Schütte, Nora; Blickle, Gerhard; Frieder, Rachel E.; Wihler, Andreas; Schnitzler, Florian; Heupel, Janis; Zettler, Ingo
The purpose of this study was to examine the relations of two facets of psychopathic personality (i.e., self-centered impulsivity and fearless dominance) with interpersonally directed counterproductive work behavior (CWB-I) and contextual performance (CP). Consistent with research on psychopathy, our hypothesis suggested that self-centered impulsivity (i.e., behavioral impulsivity characterized by disregard for rules and responsibilities) would be positively related to CWB-I and negatively related to CP. Using socioanalytic theory, we further suggested that fearless dominance (i.e., an egotistical personal style characterized by self-promotion and prioritization of one's own needs before those of others) would be negatively associated with interpersonal performance (i.e., high CWB-I and low CP) only when individuals indicated low levels of interpersonal influence (i.e., a dimension of political skill reflecting an ability to adapt one's behavior in subtle, sophisticated, and situationally effective ways). Results provided strong support for the differential relations of the psychopathic personality dimensions with the criteria of interest. Implications for theory, practice, and future research are provided in light of a number of notable strengths and limitations.